Stochastic security‐constrained economic dispatch for random responsive price‐elastic load and wind power. Issue 7 (1st August 2016) - Yang, Shengchun; Zeng, Dan; Ding, Hongfa; Yao, Jianguo; Wang, Ke; Li, Yaping
Abstract : Price‐elastic load (PEL) is a typical demand response resource. PEL provides an effective option to address the challenge of wind power output fluctuation. This study proposes a stochastic scheduling model, considering uncertainties of variable wind power and PEL response. A PEL stochastic security‐constrained economic dispatch model using chance‐constrained programming is presented for scheduling. The authors propose that the chance‐constrained transmission interface flow constraints should be considered to control the probability of transmission interface flow limit violation via the parameter of security probability. An approach is suggested to transform the stochastic model into a deterministic quadratic programming problem via linearising the branch flow constraints and transmission interface flow constraints with sensitivity analysis method. Then, the probabilistic transmission interface flow constraints are equivalently transformed into conventional constraints. Case simulations on a provincial power system with 151 buses demonstrate the effectiveness and feasibility of the proposed mechanism, models, and methods.